Studi Analisis Gedung Bertingkat dengan Perbandingan SNI-1726-2012 dan SNI-1726-2019 Terhadap Rasio Tulangan (Studi Kasus : Rumah Susun Pasar Jumat Jakarta Selatan) - Halawa, Vince Nukrisman; Isneini, Mohd; Noorhidana, Vera Agustriana; Husni, Hasti Riakara (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2022)
The design of building structures in Indonesia must be designed with the applicable earthquake regulations so that the building is resistant to earthquake loads. Over the course of time, the earthquake regulations were updated considering the large earthquakes that occurred in Indonesia still caused a lot of damage to building structures. The purpose of this study was to determine the difference between the response of the structure and the design of the structure after the SNI regulations were updated. The building being analyzed is the Pasar Jumat apartment in South Jakarta. The method used is the response spectrum method. The building was analyzed using the ETABS program given earthquake loads based on SNI-1726-2012 and SNI-1726-2019. Based on the results of the analysis, the value of the fundamental natural vibration period is not too different, the value of interstory drift between levels is below the interstory drift between permission levels and the value of the basic shear force has increased by 19.69%. While in the design of the structure, there is an increase in the ratio of reinforcement in the main beam by 10.61% at the support and 10% in the field. for secondary beam, the reinforcement ratio increased by 8.43% at the support and 10.52% in the field. While the column structure has increased by 2.84%.